Ex vivo analysis platforms for monitoring amyloid precursor protein cleavage - Kamikubo, Yuji; Jin, Hao; Zhou, Yiyao; Niisato, Kazue; Hashimoto, Yoshie; Takasugi, Nobumasa; Sakurai, Takashi (Frontiers in Molecular Neuroscience, 2023)
Alzheimer’s disease (AD) is a progressive neurodegenerative brain disorder and the most common cause of dementia in the elderly. The presence of large numbers of senile plaques, neurofibrillary tangles, and cerebral atrophy is the characteristic feature of AD. Amyloid β peptide (Aβ), derived from the amyloid precursor protein (APP), is the main component of senile plaques. AD has been extensively studied using methods involving cell lines, primary cultures of neural cells, and animal models; however, discrepancies have been observed between these methods. Dissociated cultures lose the brain’s tissue architecture, including neural circuits, glial cells, and extracellular matrix. Experiments with animal models are lengthy and require laborious monitoring of multiple parameters. Therefore, it is necessary to combine these experimental models to understand the pathology of AD. An experimental platform amenable to continuous observation and experimental manipulation is required to analyze long-term neuronal development, plasticity, and progressive neurodegenerative diseases. In the current study, we provide a practical method to slice and cultivate rodent hippocampus to investigate the cleavage of APP and secretion of Aβ in an ex vivo model. Furthermore, we provide basic information on Aβ secretion using slice cultures. Using our optimized method, dozens to hundreds of long-term stable slice cultures can be coordinated simultaneously. Our findings are valuable for analyses of AD mouse models and senile plaque formation culture models.